Ius Constituendum Formulating Basic Values of Indigenous Peoples in Constitutional Amendments - Buana, Andika Prawira; Khalid, Hasbuddin; Ma’ruf, Tri Abriana (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Regulation of Customary Law Communities in a state constitution is important to guarantee their existence and guarantee their protection. The regulation of Indigenous Law Communities in the constitution is also intended so that the regulations under the constitution can be in line with the constitution in facilitating Indigenous Law Communities.Purposes of the Research: The aim of this research is to formulate the basic principles of MHA which must be regulated in the constitution as well as efforts to amend the constitution to formulate the basic principles of MHA in the constitution.Methods of the Research: Normative legal research using case, concept and legislative approaches.Results of the Research: The basic principles of MHA that need to be formulated in the constitution include various basic values of MHA, such as having customary legal norms, having ulayat rights or traditional rights related to natural resource management, and having traditional apparatus with various characteristics that exist in each MHA. Revision of Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia as an effort to amend the constitution to include the basic principles and values of the MHA can be carried out by including basic values and principles in the MHA which include: the existence of customary legal norms, having customary rights or related traditional rights. With natural resource management, as well as having traditional apparatus with various characteristics that exist in each MHA..